TO THE ISSUE OF USING INFOCOMMUNICATION TECHNOLOGIES IN THE FORMATION OF PROFESSIONAL COMPETENCE OF TRANSLATORS (Journal of Educational Sciences, 2019)
The article is devoted to the analysis of the issue of formation of future translator's professional competence as the main factor in the construction of the educational paradigm, which allows improving the quality of professional preparation of translators and allowing to form their language personality. The article discusses the methodological potential of info-communication technologies in solving the abovementioned issue, analyzes translation as a type of speech activity. Attempts are being made to identify the didactic features of info-communication technologies and tools that underlie the use of innovative translation teaching methods and contribute to the formation of the professional competence of the future translator. The article describes the results of the pilot diagnostics monitoring in order to determine starting opportunities for first-year students and to form a positive motivational-value attitude to the translation profession. The study involved 56 students of the Abylai Khan Kazakh University of International Relations and World Languages.Keywords: translation, competence, professional competence, intercultural communication, infocommunication technologies.